A plant taxonomy for designing control experiments. - Bernstein, D. (IEEE Control systems magazine)
Control experiments can have a significant impact on control theory by forcing researchers to confront real-world issues that affect design tradeoffs and performance specifications. Sensor and actuator constraints, modeling and identification issues, and hardware imperfections must all be addressed for successful controller implementation. Control experimentation, however, is not an established discipline, and there are many fundamental issues and questions that are worthy of deep and careful consideration. In particular, the definition of a control experiment is open, as are guidelines for verification and reproducibility. The author's objectives are limited to assessing plant features that are appropriate for investigating system-theoretic problems in feedback technology. This discussion of control experimentation venues is based on a plant taxonomy; that is, a systematic classification of plant properties and the challenges they present to control experimentation and, indirectly, to control engineering practice. The article is partially motivated by Hagan et al. (1996), which lists 16 candidate plants for undergraduate control experiments. Their selection criteria are: interesting, visual, instructive, and reasonably challenging. The author is especially interested in the features of these and other plants that render them worthwhile for experimentation for either education or research. The author's objective is to provide perspective on some of the issues that arise in designing control experiments for both education and research